Search „A2, Liebesleben, 500 words“ - Anne Raveling (Babylonia)
The article discusses the teaching of foreign language reading and considers the role of AI-based tools for teachers. It focuses on a text search for authentic, level-adequate reading texts and other AI-based tools such as text analysis and image generation that support the teaching of reading competencies in German as a Foreign Language (GFL). The text search developed for teachers in the project “LATILL – Level-Adequate Texts in Language Learning“ (2022-2025)[1] is available online. A didactic example illustrates the use of the above-mentioned tools to prepare an action-oriented, internally differentiated GFL reading class. The idea is to provide practitioners with inspiration on how to use AI-based tools to plan and prepare GFL reading classes.